Global Stability of Two-Group Epidemic Models with Distributed Delays and Random Perturbation - Xiaoming Fan; Zhigang Wang; Xuelian Xu (Abstract and Applied Analysis)
We discuss a two-group SEIR epidemic model with distributed delays, incorporating random fluctuation around the endemic equilibrium. Our research shows that the endemic equilibrium of the model with distributed delays and random perturbation is stochastically asymptotically stable in the large. In addition, a sufficient stability condition is obtained by constructing suitable Lyapunov function.